Noble gas ion beams in materials science for future applications and devices. (8th September 2017) - Belianinov, Alex; Burch, Matthew J.; Kim, Songkil; Tan, Shida; Hlawacek, Gregor; Ovchinnikova, Olga S.
Abstract: Abstract : Helium ion microscopy (HIM), enabled by a gas field ion source (GFIS), is an emerging imaging and nanofabrication technique compatible with many applications in materials science. The scanning electron microscope (SEM) has become ubiquitous in materials science for high-resolution imaging of materials. However, due to the fundamental limitation in focusing of electron beams, ion-beam microscopy is now being developed (e.g., at 20 kV the SEM beam diameter ranges from 0.5 to 1 nm, whereas the HIM offers 0.35 nm). The key technological advantage of the HIM is in its multipurpose design that excels in a variety of disciplines. The HIM offers higher resolution than the best available SEMs as well as the traditional gallium liquid-metal ion source (LMISs) focused ion beams (FIBs), and is capable of imaging untreated biological or other insulating samples with unprecedented resolution, depth of field, materials contrast, and image quality. GFIS FIBs also offer a direct path to defect engineering via ion implantation, three-dimensional direct write using gaseous and liquid precursors, and chemical-imaging options with secondary ion mass spectrometry. HIM covers a wide range of tasks that otherwise would require multiple tools or specialized sample preparation. In this article, we describe the underlying technology, present materials, relevant applications, and offer an outlook for the potential of FIB technology in processing materials.